Influence of health swimming lessons on the physical development of women 18–25 years old - Шейко, Лилия (Slobozhanskyi Herald of Science and Sport, 2018)
Liliia Sheiko Purpose: determine the degree of influence of health swimming lessons on changes in the physical development of women 18–25 years of age. Material & Methods: the study involved 30 women 18–25 years. Data collection was carried out in the physical culture groups of the Author's School of Swimming Yu. V. Bliznyuk and the Pioner pool (public educational institution sport school for water sports Yana Klochkova). Subjects had the same swimming readiness. Applied: interrogation, testing, instrumental methods of studying the cardiovascular system. The obtained quantitative data were processed by methods of mathematical statistics. Results: the study suggests that in women 18–25 years of health swimming exercises cause positive changes in physical development. In both groups of studied events, significant changes in anthropometric indicators and indicators of the state of the cardiovascular system. Significant improvement in indicators The most characteristic is revealed after a year of regular studies. Conclusion: swimming exercises positively influenced the anthropometric indicators of women aged 18–25. It has been established that there have been significant improvements in the indices of the functional state of the cardiovascular system of women swimming. It was revealed that the anthropometric indices and indices of the functional state of the cardiovascular system after a year of occupations in comparison with the initial data were significantly high (P(t)<0,01; P(t)<0,001).